A software package for the representation and optimization of water reservoir operations in the VIC hydrologic model. (April 2020) - Dang, Thanh Duc; Vu, Dung Trung; Chowdhury, A.F.M. Kamal; Galelli, Stefano
Abstract: Macroscale hydrological and land surface models increasingly rely on novel streamflow routing algorithms that explicitly account for the presence of engineered water storages, which largely affect river basin dynamics. In this short communication, we contribute to this growing field by presenting VIC-ResOpt, a software package for the representation and optimization of water reservoirs in the routing model commonly used as a post-processor with the Variable Infiltration Capacity (VIC) hydrologic model. VIC-ResOpt comprises tools for simulating different reservoir operating approaches, optimizing operations, and exploring the sensitivity of the model output with respect to the parameterization of the operating rules. The package relies on automated scripts and optimization engines, thereby requiring minimal user effort. We demonstrate some of its functionalities in the upper portion of the Chao Phraya river basin (Thailand), which is regulated by two large dams. Highlights: Explicit representation of water reservoirs in the VIC hydrologic model. Simulation and optimization of both rule curves and operating rules. Powered by state-of-the-art optimization algorithms. VIC-ResOpt can support regional and global studies on regulated river basins.